Bond strength of composite resin restoration repair: Influence of silane and adhesive systems - Gutierrez, Natália C. [UNESP]; Moecke, Sabrina E. [UNESP]; Caneppele, Taciana M.F. [UNESP]; Perote, Letícia C.C.C. [UNESP]; Batista, Graziela R. [UNESP]; Huhtalla, Maria F.R.L. [UNESP]; Torres, Carlos R.G. [UNESP] (Jaypee Brothers Medical Publishing, 2019)
Aim: The aim of this study is to evaluate the effect of silane (Si) application and different adhesive systems on the bond strength of composite resin repair. Materials and methods: One hundred composite truncated cone-shaped specimens were prepared and submitted to 5,000 thermal cycles to simulate existing restorations. Their top surfaces were airborne particle abraded with aluminum oxide, etched with phosphoric acid, and divided into two groups (n = 50) with or without Si application. Each group was divided into five subgroups (n = 10) according to the adhesive system applied: Solobond Plus Primer and Adhesive (SPA)-two-bottle, Solobond Plus adhesive (SA), Admira Bond (A)-one bottle, Futurabond DC (FDC)-self-etch, and Futurabond M (FM)-self-etch. New composite resin was applied over the bonded area. A control group was prepared to evaluate the cohesive strength of the composite resin. Specimens were submitted to tensile stress. Data were analyzed with two-way analysis of variance (ANOVA), and the Tukey and Dunnett tests. Results: Si application reduced the bond strength of all adhesives (p = 0.001). Groups SA and SPA showed higher bond strengths in relation to other groups (p = 0.01). Groups FDC + Si, FM, FM + Si, and A + Si showed smaller mean bond strength values than that of the control group (p < 0.05). Conclusion: Previous Si application reduced bond strength values. The two-bottle adhesive showed better results than one-bottle or self-etching systems for composite resin repairs. Clinical significance: The kind of adhesive system applied for composite resin repairs has a great influence on bond strength values. The use of Si in this situation is not recommended.
Keywords: Adhesive system; Composite resin repair; Laboratory research; Tensile bond strength